1998
DOI: 10.1046/j.1365-2648.1998.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of questioning strategies by clinical teachers

Abstract: By using questioning and other appropriate teaching strategies, clinical teachers can facilitate the development of critical thinking, decision making and problem solving in students. This study examined clinical teachers' use of questioning and the variations in their use of questioning as a teaching strategy. Although there was a variation in the number of questions asked, predominantly low level questions were asked by 26 clinical teachers at two post-clinical conferences. Based on the findings of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
56
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 16 publications
(11 reference statements)
15
56
0
1
Order By: Relevance
“…In a similarly designed study, Sellappah and colleagues found that during practicebased experiences, clinical instructors asked lower-level questions 91.2% of the time. 13 Further, the clinical instructors' years of experience as a practitioner or teacher were not correlated with their propensity to ask loweror higher-order questions. A study by Phillips and Duke compared the cognitive level of questions asked by fulltime clinical faculty members and volunteer preceptors in nursing programs.…”
Section: Taxonomy Of Questionsmentioning
confidence: 89%
See 3 more Smart Citations
“…In a similarly designed study, Sellappah and colleagues found that during practicebased experiences, clinical instructors asked lower-level questions 91.2% of the time. 13 Further, the clinical instructors' years of experience as a practitioner or teacher were not correlated with their propensity to ask loweror higher-order questions. A study by Phillips and Duke compared the cognitive level of questions asked by fulltime clinical faculty members and volunteer preceptors in nursing programs.…”
Section: Taxonomy Of Questionsmentioning
confidence: 89%
“…Unfortunately, observations of classroom-based instructors have repeatedly shown that lower-order questions are far more frequently used. 11,13 Perhaps teachers do not value higher-order questions and feel they are not effective, or perhaps a lack of formal training on how to formulate questions to stimulate learning is the root cause. 4 There is a paucity of empirical data regarding how to most effectively use questions to teach.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers often rely heavily on recall-based questions that fail to stimulate deeper thinking and can cause learners to disengage. 3,4 Questions that are mismatched to learner level can be equally problematic; asking novice learners unrealistically challenging questions can lead them to lose self-confidence and interest and asking advanced learners fact-based questions can demotivate them. Finally, questions posed in a seemingly confrontational manner (which can cause anxiety in learners and may be perceived as "pimping") can adversely affect the learning climate.…”
mentioning
confidence: 99%